Analysis on the Competitive Strategy of Burger Shot in Malang and Surabaya Market - Lisfiansyah, Adrian (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2018)
This study aims to analyze the strategy of Burger Shot in the fierce market of Malang and Surabaya. The data of this qualitative descriptive study were collected through interviews and observations and were analyzed using EFE matrix, IFE matrix, CPM matrix, SWOT matrix, IE matrix and QSPM matrix.The results of external environmental analysis show that the company's response to its external environment is above average, but there are some untapped opportunities and serious threats that can disrupt the restaurant’s performance. The internal condition analysis result shows that Burger Shot has strong internal strengths, but there are still weaknesses that become problems and opportunities that must be used to increase its internal strength and cover its weakness. The competition analysis results show that Burger Shot is still below Burger King and Carls Jr. in Surabaya market but above Eat Two - Burger Bar in Malang market.The results of strategy selection analysis show that the appropriate strategy for the restaurant is growing and developing, or intensive strategy, and the recommended strategy is market penetration by implementing marketing strategy in increasing the number of salespeople, increasing the advertising burden, increasing the publication business and utilizing digital marketting trend with social media into an effective strategy and offer a burger shot product sales promotion extensively.Keywords: environmental analysis, alternative strategy, competitive strategy